Transition from school to VET in German-speaking Switzerland - Brahm, Taiga [Verfasser]; Euler, Dieter [Verfasser]; Steingruber, Daniel [Verfasser] (My University, 2014)
"The transition from school to vocational education and training is becoming more difficult for an increasing number of adolescents. Despite the growing significance of 'interim solutions' (IS) shaping the pathway after compulsory education, there is hardly any research. This study aims at contributing to this research gap by investigating IS in the German-speaking part of Switzerland. The research explored three research questions: (1) How can the target group of ISs be characterised - especially regarding social and personal resilience factors? (2) Which goals regarding the adolescents' development are pursued? (3) How are the curriculum and the learning activities designed to facilitate the adolescents' development? Based on literature analysis, semi-structured expert interviews and case studies in five institutions in three Swiss cantons were conducted. The case analyses showed that the IS put different emphasis on the two kinds of objectives: (a) vocational choice and preparation and (b) personality development." (Autorenreferat; BIBB-Doku)
Keywords: P 1.1 Jugendliche; G 1.3.2.2 Übergänge; I 2.2.1 Westeuropa; Jugendlicher; Berufseinmündung; Erste Schwelle; Berufsvorbereitung; Übergangssystem; Berufsorientierung; Persönlichkeitsentwicklung; Schweiz